Evaluation of the Leadership Management Training Program Based on Kirkpatrick's Model of Lecturer Performance at Tangerang Raya University - Ratnasari, Ani; Joko Dewanto, Ignatius; Praditia, Dimas; Santos, Andik (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
Determining employee potential to support training and career development as well as positions in human resources is not easy. One way to evaluate is that Kirkpatrick's model influences performance effectiveness, as well as the effectiveness of the training programs that have been implemented. The aim is to find out leadership management training for Higher Education Lecturers. The population in this study were participants in leadership management training at the University of Tangerang Raya. Use of data based on primary data (questionnaire). The sampling technique used is non-probability sampling using the proportional random sampling method. With the number of research samples, there were 35 lecturers at the University of Tangerang Raya located in Tigaraksa. The dependent variable is performance. The independent variables are Kirkpatrick's attributes: reaction, learning, behavior, and result. This study provides recommendations for evaluating leadership management training using the cryptic method affecting performance, explaining that there is no training carried out in leadership management training activities that do not affect HR performance in the University of Tangerang Raya. Follow-up research conducts training according to competency standards that are following the needs of Lecturer HR.